Diagnostic differences in the pharmacologic response to cholecystokinin and amyl nitrite in patients with absent contractility vs type I Achalasia. Issue 8 (29th April 2020) - Babaei, Arash; Shad, Sadaf; Massey, Benson T.
Abstract: Background: Absent esophageal contractility (AC) is distinguished from type 1 achalasia (ACH1) during high‐resolution manometry (HRM) on the basis of normal or elevated deglutitive integrated relaxation pressure (IRP) values. However, IRP measurements are subject to pressure recording error. We hypothesized that distinctive responses to pharmacologic provocation using amyl nitrite (AN) and cholecystokinin (CCK) could reliably distinguish AC patients from those with ACH1. Aim: To compare esophageal response with AN and CCK in a well‐defined cohort of ACH1 and AC patients. Method: All available clinical, radiographic, endoscopic, and manometric information in 34 patients with aperistalsis was reviewed to determine the final diagnosis of ACH1 and AC. The differences in response to provocative challenges with the rapid drink challenge (RDC) test and administration of AN and CCK were compared between these two groups. Results: Eighteen patients were diagnosed with ACH1 and sixteen with AC. While IRP values were significantly higher in ACH1, the standard criterion value misclassified four AC patients as having ACH1 and five ACH1 patients as having AC. IRP values on the RDC did not accurately segregate AC from ACH1, but we were able to identify AN and CCK esophageal motor response criteria that allowed correct classification of ACH1 and AC patients. Conclusions: Nearly a quarter of AC and ACH1 patients may be misdiagnosed based on manometric IRP criteria alone. Differences in the esophageal motor responses to AN and CCK have the potential to facilitate the correct diagnosis in these challenging patients. Abstract : Esophageal pressure topography plots of supine wet swallows misdiagnosed as absent contractility and type 1 achalasia based on normal (top left) and abnromal (lower left) integrated relaxation pressure (IRP) respectively. Cholecystokinin (CCK) in a true type 1 achalasia (despite normal IRP) patient induces a paradoxical lower esophageal sphincter (LES) contraction (top right), and in true absent contractility (despite abnormal IRP) induces LES relaxation (lower right).